Pendampingan Ibu Nifas dalam Penggunaan Aromaterapi Essential Oil Melati Penurunan Postpartum Blues - Meilisya Pohan; Nur ' Aini Dalimunthe; Yulia Kusumanti3 (Information Technology and Science (ITScience), 2025)
Management of postpartum mothers with postpartum blues can be carried out through pharmacological and non-pharmacological treatments. Often, postpartum sadness goes unrecognized and, consequently, can develop into clinical postpartum depression. Various efforts have been made to overcome postpartum sadness, one of which is the use of aromatherapy. The purpose of this study is to determine the effectiveness of jasmine aromatherapy in reducing postpartum depression. This study concludes that aromatherapy with jasmine essential oil is proven effective in accelerating the reduction of postpartum sadness in Bangun Sari Village, Silau Laut District. Midwives should communicate this to postpartum mothers to help them manage postpartum sadness, including through education and alternative treatments for postpartum depression using aromatherapy.